Systematic review of brucellosis in Kenya: disease frequency in humans and animals and risk factors for human infection - J. Njeru; G. Wareth; F. Melzer; K. Henning; M. W. Pletz; R. Heller; H. Neubauer (BMC Public Health, 2016)
Abstract Background Brucellosis is a debilitating zoonotic disease affecting humans and animals. A comprehensive, evidence-based assessment of literature and officially available data on animal and human brucellosis for Kenya are missing. The aim of the current review is to provide frequency estimates of brucellosis in humans, animals and risk factors for human infection, and help to understand the current situation in Kenya. Methods A total of accessible 36 national and international publications on brucellosis from 1916 to 2016 were reviewed to estimate the frequency of brucellosis in humans and animals, and strength of associations between potential risk factors and seropositivity in humans in Kenya. Results The conducted studies revealed only few and fragmented evidence of the disease spatial and temporal distribution in an epidemiological context. Bacteriological evidence revealed the presence of Brucella (B.) abortus and B. melitensis in cattle and human patients, whilst B. suis was isolated from wild rodents only. Similar evidence for Brucella spp infection in small ruminants and other animal species is unavailable. The early and most recent serological studies revealed that animal brucellosis is widespread in all animal production systems. The animal infection pressure in these systems has remained strong due to mixing of large numbers of animals from different geographical regions, movement of livestock in search of pasture, communal sharing of grazing land, and the concentration of animals around water points. Human cases are more likely seen in groups occupationally or domestically exposed to livestock or practicing risky social-cultural activities such as consumption of raw blood and dairy products, and slaughtering of animals within the homesteads. Many brucellosis patients are misdiagnosed and probably mistreated due to lack of reliable laboratory diagnostic support resulting to adverse health outcomes of the patients and routine disease underreporting. We found no studies of disease incidence estimates or disease control efforts. Conclusion The risk for re-emergence and transmission of brucellosis is evident as a result of the co-existence of animal husbandry activities and social-cultural activities that promote brucellosis transmission. Well-designed countrywide, evidence-based, and multidisciplinary studies of brucellosis at the human/livestock/wildlife interface are needed. These could help to generate reliable frequency and potential impact estimates, to identify Brucella reservoirs, and to propose control strategies of proven efficacy.